2022
DOI: 10.1021/acs.chemrestox.2c00017
|View full text |Cite
|
Sign up to set email alerts
|

Increased JUUL Emissions from Initial Puffs after Removing and Reinserting Pod

Abstract: Standard laboratory electronic cigarette (ECIG) puffing protocols that do not consider user behaviors, such as removing and resinserting a pod, may underestimate emissions. This study compared JUUL emissions from four 10-puff bout procedures. We generated ECIG aerosol in a chamber using a JUUL device and measured concentrations of particulate matter ≤2.5 μm in diameter (PM2.5). The JUUL pod was removed and reinserted 0 times, 1 time, 4 times, and 9 times in experiments 1–4, respectively. Mean real-time PM2.5 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The emissions return to normal when the bubbles are detached from the wick by flicking, removing and reinstalling, or squeezing the pod. 21,22 We also observed that toxicant emissions from aftermarket pods generally exhibited higher variability than JUUL pods (Table 1). This variability was the most pronounced for W01 (RSD: 57% for ROS compared to 14% for JUUL and 104% for CCs compared to 38% for JUUL), and we suspect it stems from looser manufacturing tolerances.…”
Section: ■ Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The emissions return to normal when the bubbles are detached from the wick by flicking, removing and reinstalling, or squeezing the pod. 21,22 We also observed that toxicant emissions from aftermarket pods generally exhibited higher variability than JUUL pods (Table 1). This variability was the most pronounced for W01 (RSD: 57% for ROS compared to 14% for JUUL and 104% for CCs compared to 38% for JUUL), and we suspect it stems from looser manufacturing tolerances.…”
Section: ■ Discussionmentioning
confidence: 64%
“…The buildup of bubbles can prevent full wetting of the coil by the liquid, leading to decreased emissions. The emissions return to normal when the bubbles are detached from the wick by flicking, removing and reinstalling, or squeezing the pod. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle size distribution and concentration are essential factors in estimating the potential adverse health effects of vaping [ 35 ]. However, these variables are highly influenced by device usage behavior [ 3 , 36 , 37 ], and monitoring conditions like air change rate, temperature, and relative humidity [ 3 , 7 ]. Therefore, the characterizations of ENDS emissions tend to be dependent on study design, which could lead to uncomparable or inconsistent results among studies [ 19 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECIG devices utilize an atomizer to produce the airborne contaminants containing particulate matter (PM) and volatile organic compounds (VOCs) ( Fernández et al ., 2015 ; Tzortzi et al ., 2018 ; Marcham and Springston, 2019 ). Much of the current laboratory research on ECIGs is conducted using an airborne exposure chamber, which allows the measurement of aerosol emissions generated from ECIGs in a controlled environment ( Czogala et al ., 2014 ; Geiss et al ., 2015 ; Cunningham et al ., 2020 ; Soule et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%